URGENCY OF THE DRAFT STATUTE ON MATERNAL AND CHILD WELFARE FOR FEMALE EMPLOYEES - Nisa, Ardina Khoirun (Yurisprudentia: Jurnal Hukum Ekonomi, 2023)
The ongoing deliberations involve the Draft Statute on Maternal and Child Welfare, with particular emphasis on several regulations that prioritize the well-being of mothers and children. This study emphasizes the initial 1000 days of an individual’s life, commencing from the prenatal stage, commonly referred to as the "golden age," with the objective of cultivating a high-caliber generation. The objective of this study is to examine the underlying justifications for the necessity of the Draft Statute on Maternal and Child Welfare, as well as the obstacles encountered during the implementation of said legislation. The study employed normative legal research methodology, adopting a statutory approach and utilizing secondary data collection through a literature review employing qualitative descriptive data analysis techniques. The findings of this study indicate that the implementation of the Draft Statute on Maternal and Child Welfare is necessary in order to facilitate the development of Indonesia’s future generations. Nevertheless, the implementation of the Draft Statute on Maternal and Child Welfare may pose a challenge in terms of reduced female employee recruitment, as it is perceived to have negative implications for companies. This will serve as the foundation for companies to establish specific measures in the recruitment of female employees.